1996
DOI: 10.1007/bf00868517
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir treatment of relapsing-remitting multiple sclerosis

Abstract: Acyclovir treatment was used in a randomized, double-blind, placebo-controlled clinical trial with parallel groups to test the hypothesis that herpes virus infections are involved in the pathogenesis of multiple sclerosis (MS). Sixty patients with the relapsing-remitting form of MS were randomized to either oral treatment with 800 mg acyclovir or placebo tablets three times daily for 2 years. The clinical effect was investigated by an extensive test battery consisting of neurological examinations, neuro-ophtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(25 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…The present results do not answer the question of whether EBV dysregulation is consequence or cause of MS but disclose a link between EBV reactivation, antiviral immune response and disease activity during the relapsing-remitting stage of MS. Such a scenario is consistent with the results of randomized, double-blind, placebo-controlled clinical and MRI studies of anti-herpesvirus therapy in relapsing-remitting MS showing that anti-herpesvirus drugs inhibiting viral replication have beneficial effects in subgroups of patients with higher exacerbation rates and more severe disease activity [59], [60]. Further work is needed to better understand whether and how an altered balance between EBV and the host immune system contributes to MS onset and verify the potential benefits of new antiviral drugs in controlling MS [61].…”
Section: Discussionsupporting
confidence: 86%
“…The present results do not answer the question of whether EBV dysregulation is consequence or cause of MS but disclose a link between EBV reactivation, antiviral immune response and disease activity during the relapsing-remitting stage of MS. Such a scenario is consistent with the results of randomized, double-blind, placebo-controlled clinical and MRI studies of anti-herpesvirus therapy in relapsing-remitting MS showing that anti-herpesvirus drugs inhibiting viral replication have beneficial effects in subgroups of patients with higher exacerbation rates and more severe disease activity [59], [60]. Further work is needed to better understand whether and how an altered balance between EBV and the host immune system contributes to MS onset and verify the potential benefits of new antiviral drugs in controlling MS [61].…”
Section: Discussionsupporting
confidence: 86%
“…viral replication, but have limited effects on latent EBV infection, and trials in MS have been inconclusive. 36, 73, 74 Thus at this time the only practical implications may be diagnostic – EBV negativity or low anti-EBNA titers in an individual with CIS would suggest a diagnosis other than MS. 70 …”
Section: Specific Risk Factorsmentioning
confidence: 99%
“…Hence antiviral drugs may be able to reduce the relapse rate in multiple sclerosis patients. The first and largest study to investigate the effect of an antiviral drug, acyclovir, has been reported in Lycke et al (1996). The acyclovir study was a randomized, placebo-controlled, double-blind clinical trial, where 60 multiple sclerosis patients were randomly assigned to acyclovir and placebo, and then followed for two years.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Similar in spirit are multiple sclerosis clinical trials where information on patient relapses before randomization is available. For example in the randomized placebo-controlled trial described in Lycke et al (1996), relapses that occurred in the two years preceding randomization were recorded. Such settings can also be seen to correspond to a switch of treatment, where before randomization, patients receive standard treatment, and after randomization, some patients are switched to the experimental treatment.…”
Section: Introductionmentioning
confidence: 99%